NILAI RELIGI DALAM NOVEL–NOVEL KARYA ASMA NADIA - Herni Tri Yuwana (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2018)
This study aims to describe the value of religion in the novel-novel by Asma Nadia covering aqidah, syariah, and morals. This research method using qualitative descriptive method. Research data is sourced from the novel "Assalamualaikum Beijing" and "Hijab Traveler Love Sparks In Korea" by Asma Nadia. Using the technique of data collection documentation, refer to, and note. The results showed that the value of religion in the novel-novel by Asma Nadia covers three aspects, namely: (1) the creed; (2), and (3) moral. The value of belief include: (a) monotheism, (b) confidence in the existence of the supernatural, and (c) faith towards destiny. Sharia value include: (1) worship (say the creed, working on the prayer, zakat/alms, fasting, and Hajj), (2) muamalah (loan borrowing), (3) Munakahat (family relations, marriage, divorce, maintenance of the child, guidelines for a husband and wife), (4) Siyasa (brotherhood, deliberation, tolerance, and responsibility), (5) Morals (gratitude, patience, tawadhu, forgiving, tawwakul, istiqoma, dare and do good to parents). Moral values include: (1) the morals of Allaah (Dhikr, prayers, praying, tawwakul), (2) morals to both parents (worship, serve, and respect both parents), (3) attitudes, in accepting the provisions of God (predestination, the nature of the good and the bad). (4) the feeling of shame (shame, shame towards others and yourself).